Antioxidant Capacities of Pueraria mirifica, Stevia rebaudiana Bertoni, Curcuma longa Linn., Andrographis paniculata (Burm.f.) Nees. and Cassia alata Linn. for the Development of Dietary Supplement - Buran Phansawan,; Supak Poungbangpho, (Agriculture and Natural Resources, 2007)
This work reported on the antioxidant capacities of five different medicinal plants generally found throughout the country. The medicinal plants including Pueraria mirifica, Stevia rebaudiana Bertoni, Curcuma longa Linn., Andrographis paniculata (Burm.f.) Nees. and Cassia alata Linn. were subjected to extraction using a variety of solvents including ethanol, methanol, acetone, acetic acid, and distilled water. The method was based on inhibition in absorption of ABTS [2,2/-azino-bis (3-ethylbenthiazoline-6-sulfonic acid)] technique and the antioxidant capacity was recorded as TEAC (Trolox equivalent antioxidant capacity). The result showed that ethanol was the best solvent for extraction of all five medicinal plants to give the highest antioxidant capacities, followed by acetone, methanol, distilled water, and acetic acid, respectively. The highest antioxidant capacity was found in Stevia rebaudiana Bertoni., followed by Cassia alata Linn., Curcuma longa Linn., Andrographis paniculata (Burm.f.) Nees., and Pueraria mirifica, respectively. Moreover, the interaction effect between solvents and medicinal plants on antioxidant capacity showed that the highest antioxidant capacity was found in Stevia rebaudiana Bertoni extracted with acetone (2.96) and methanol (2.85), followed by Stevia rebaudiana Bertoni extracted with ethanol (2.64), and Cassia alata Linn. extracted with ethanol (2.57), while, the lowest antioxidant capacity was found in Andrographis paniculata (Burm.f.) Nees. extracted with acetone (0.04).